RESPONSE OF TWO SUNFLOWER (HELIANTHUS ANNUUS L.) GENOTYPES TO VA-MYCORRHIZAL INOCULATION AND PHOSPHORUS LEVELS - C.P. CHANDRASHEKARA, V.C. PATIL; V.C. PATIL; M.N. SREENIVASA (BIOTROPIA, 1995)
The performance of two sunflower genotypes (Morden and MSFH-8) with and without VA-mycorrhizal fungi at three P levels (38, 56 and 75 kg P2O5 ha -1 ) in vertisol of Dharwad was studied to determine the effect of mycorrhizal inoculation on plant growth, yield and P uptake. The results showed that the VAM inoculation increased sunflower yield (14%), total biomass (16%), oil content (3.1%) and P uptake (30.5%) over uninoculated control. The percent root colonization and chlamydo-spore count decreased with increasing P levels. The total biomass production, seed yield and P uptake of mycorrhizal plants at 38 kg P2O5 ha -1 more than the non-mycorrhizal plants at 75 kg P2O5 ha -1 . The biomass and seed yield of mycorrhizal plants at same P level were more than the non-mycorrhizal plants. Mycorrhizal plants of Morden at 38 kg P2O5 ha -1 and MSFH-8 at 56 kg P2O5 ha -1 produced higher seed yield, oil content and total biomass than non-mycorrhizal plants supplied with 75 kg P2O5 ha -1 . The results indicated that, VA-mycorrhizal inoculation helps in saving 25 and 50 percent of recommended dose of phosphatic fertilizer (75 kg P2O5 ha -1 ) in MSFH-8 (single cross hybrid) and Morden (open pollinated variety), respectively. Key words: Mycorrhizas/Plant nutrition/Inoculum/Glomus fasciculatum/Helianthus annuus/Phosphorus fertilizers/Metabolism.